A Comparative Study between Conventional Pap Smear and Liquid-Based Cytology: A Clinco-Cytological Study of Iraqi Women with Some Health Problems of Cervix - Alabbody, Huda Hameed K.; Al-Ghuraibawi, Zahraa Adnan G. (Iraqi Journal of Science, 2019)
A cervical screening by Pap test is necessary in recognizing precancerous and cancerous cases to reduce mortality due to cervical cancer among women. Regular screening and follow up can make it easier to early diagnose and eventually, to treat and control cervical cancer. This study aimed to detect atypical pathological changes of the vagina and uterine cervix of a sample of Iraqi women by macro- and micro-examination, and to determine the link with the demographic features. Also the study aimed to evaluate the two Pap smear techniques; the conventional and the base liquid methods. The study included 50 women with genital health problems (18-50 years old) who were referred to the National Cancer Research Center (NCRC), the University of Baghdad, during the period from 1st April to 30st of September 2018. Both visual inspection of the uterine cervix and Papanicolaou smear were performed for all of the participants. The results showed that most patient women (96%) were married and sexually active, with 51% being married under 20 years of age .Visual inspection of the cervix showed that 30% of the women had translucent, opaque or erosion lesions. Upon cytology examination, 92% of the women showed nonspecific inflammation, 70% revealed reactive squamous metaplasia, 10% had Koilocytotic atypia, and 8% suffered from cervical intraepithelial neoplasia (CIN1) or low grade squamous intraepithelial lesion (LGSIL). Contraception was used by 82% of the patients, while 36% used pills. The causes of the referral to the centre were abnormal vaginal discharge (44%) and post-coital bleeding "and\or" dyspareunia (20% each). Lastly, 74% of the participants did not make this test previously. Liquid-based cytology technique outperformed conventional pap smears because of improved fixation, decreased impurities factors, and standardization of cell transfer. We conclude that routine screening and Pap smear testing for uterine cervix and vagina might be useful to prevent the occurrence of precancerous lesions in the genital system of sexually active women. We recommend to apply this test before and after treatment and to activate the cellular examination in the basal fluid method